Arctic hiking mattress from processed reindeer pelt - Mäntysalo, E.; Marjoniemi, M.; Nieminen, M. (Rangifer, 1996)
Quality of clothing and equipment has always been the most important matter when hiking in extreme, arctic conditions. Reindeer (Rangifer tarandus) hides were processed with the aid of irreversible tannage and careful hydrophobic treatment. As a result, a processed reindeer-pelt hiking mattress was obtained, superior to the best hiking mattresses on the market made of plastic materials. Its physical properties are: weight 1.7 kg, width 60 cm and length 190 cm. The reindeer pelt has a low initial isothermal compressibility, 0.71 Pa-1, a low thermal conductivity, 0.070 Wm-1°C-1, and an R-value of 0.35 m2°CW-1. The heat-flow experimenrs have been carried our at a pressure of 810 Pa. In addition, the reindeer pelt stays dry in use because of its good ventilation. In these respects the reindeer pelr is superior to plastic mattresses.